Wien als Festungsstadt im 16. Jahrhundert Zum kartografischen Werk der Mailänder Familie Angielini - Opll, Ferdinand (2017)
Three members of the Milan-born Angielini family have bequeathed plans and views of fortified places at the border to the Ottoman Empire around 1570, amongst them three maps of Vienna. This basis serves for an analysis of Vienna's development into a fortress city. Written sources and archaeological evidence are also used, as are insights from environmental history. Early modern fortress-construction in theory and practice and the cartographic documentation of the Hungarian area and Vienna, both seen in a supraregional context, compose further important chapters of the book.